Approaches to supervising work-based learning students' workplace research. Issue 1 (11th February 2014) - Talbot, Jon; Lilley, Andy
Abstract : Purpose: – The purpose of this paper is to outline a small research project designed to explore the practices of the UK work-based learning (WBL) tutors in facilitating formal research projects in the workplace. Design/methodology/approach: – Data were collected using a short questionnaire to practitioners administered electronically and a daylong workshop where issues were discussed in greater depth by participating tutors. Findings: – The main findings are that there is a degree of agreement by WBL tutors about the distinctiveness of WBL research projects; that although there is increasing use of technology to support delivery only one institution is using e-learning as the principal means of delivery; emphasis is upon a relatively small number of techniques and there is a strong preference for qualitative over quantitative methods. Research limitations/implications: – The main limitation of the study is the relatively small number of active participants. However, this is the only study of its kind and the results offer insights into an important element of pedagogic practice in WBL. Practical implications: – The project enabled the identification of common approaches and facilitated discussion of problems shared by WBL tutors across the field. There appears to be a consensus that situated investigation exists within a different contextual framework to traditional academic dissertation projects and that the focus is therefore necessarily on generating data as the basis for active problem solving. Originality/value: – This is the only empirical study of practice in respect of facilitating research projects on WBL programmes in higher education.